The Influential Factor Analysis of Classification Partition Management Mode on the Emergency Triage - Zhang NA; Cui HUAIXIN (Tehran University of Medical Sciences, 2016)
Background: The aim of the study was to discuss on the influential factors of the mode of classification of partition management in the emergency triage. Method: Retrospectively analyzing the effects of emergency triage of 156 cases who adopted the classification partition management mode during Oct 2014 to Oct 2015 in Xuzhou Central Hospital (Xuzhou, Jiangsu Province, China). They were divided into triage success group of 108 cases and triage failure group of 48 cases. Comparing the single factor analysis and multi-factor analysis, and selecting possible influential factors. Result: According to the single factor analysis, for the patients who came to the doctor in the daytime and working days, the higher education degree and compliance they had, the faster the back-show time of emergency inspect and check came back, the more comprehensive the body examination and disease history taking were done, the simpler the disease condition was, the higher triage success rate they received. Compared to the emergency observation time between two groups, the difference was not statistically significant. According to the multi-factor analysis, the emergency check and examination back-show time, the comprehensive degree of body examination and disease history taking and the complexity degree of disease could be the independent risk factors for triage success. Conclusion: Simplify the examination procedure, improve the efficiency of back-show and acquire detail disease information are important methods for the improvement of triage success.